Vaccination with inactivated SARS-CoV-2 vaccine TURKOVAC induces durable humoral and cellular immune responses up to 8 months - Yılmaz, Seçil; Eken, Ahmet; Sezer, Zafer; Bağcı, Burcu Şen; Erdem, Serife; Sarıkaya, Medine Doğan; Kaplan, Busra; Inal, Ahmet; Bayram, Adnan; Kalın Unuvar, Gamze; Zararsız, Gokmen; Yerlitas, Serra İlayda; et al. (Frontiers in Medicine, 2025)
BackgroundThe rapid spread of the SARS-CoV-2 virus has led to a global health crisis, necessitating swift responses in medical science, mainly through vaccination strategies. While short-term vaccine effectiveness is evident, immune protection’s long-term effects and duration remain incompletely understood. Systematic monitoring of these responses is essential for optimizing vaccination strategies.AimsThis study aimed to explore the durability of antigen-specific T and B cell responses and antibody levels up to 8 months post-immunization with the inactivated TURKOVAC vaccine in volunteers. Additionally, the impact of two versus three doses of vaccination on these parameters was analyzed.MethodsVolunteers (n = 80) received two or three doses of TURKOVAC. Spike-specific B cells, CD4+ T cells, CD8+ T cells, and antibody levels were measured at multiple time points post-immunization.ResultsSpike-specific B cells remained elevated up to 8 months post-immunization. SARS-CoV-2-specific CD4+ and CD8+ T cells peaked at 4 months but declined thereafter. TURKOVAC resulted in durable antigen-specific humoral and cellular immune memory with distinct kinetics. Still, most assessments observed no significant differences between two and three doses, except for antigen specific-IL-2 and CD4+ LAMP1 responses.ConclusionTURKOVAC vaccination induces durable immune responses, with spike-specific B cells persisting up to 8 months and T cell responses peaking at 4 months before declining. These findings suggest that TURKOVAC contributes to long-term immune protection against SARS-CoV-2.